Patients' awareness about Cardiovascular Disease and the Causes of Coronary Artery Disease - hussein, Ahmed (Iraqi National Journal of Nursing Specialties, 2012)
Objective: This study aims to assess the awareness of patients suffering from cardiovasculardiseases.Methodology: A descriptive design was applied in this study. A purposive sample consisted of(100) patients with cardiovascular disease in the Mosul's hospitals were interviewed to achieve studyobjectives. A questionnaire was used for data collection after tested for validity and reliability by pilotstudy.Results: The study results showed the mean of patients awareness are (1.78) cut point of (3) andthe majority of patients84% were aged more than 50 years or above. Slightly increase proportion ofmale more than females. Most of them are married81%, retired, smokers, and a period of developingthe disease are less than one year47%.Recommendations: the study recommended the need for targeted education regarding riskfactors, especially those who are treated for hypertension and diabetes mellitus.